عصر حاضر میں توہین رسالتﷺ کے قوانین: عمل درآمد کی ضرورت ،صورتیں اورعملی تدابیر: Laws of blasphemy in Modern Times; Need for implementation, cases and practical measures - Ghulam Mustafa; Dr Zia Ullah; Dr. Sajjad Ahmed (Al Manhal Research Journal, 2023)
Blasphemy against the revered personality of Prophet Muhammad (peace be upon him) is an act of disobedience. To address such actions, it is necessary to have appropriate laws in place. In line with this, many Muslim countries, including Pakistan, have implemented laws to safeguard the honor of Prophet Muhammad (peace be upon him). These laws have been incorporated into the constitution of Pakistan. As per these laws, no individual is allowed to engage in blasphemy towards the Prophet Muhammad (peace be upon him), and those found guilty will face legal consequences, which are considered a grave offense based on Islamic principles. In the present era, there are instances of blasphemy occurring in different countries, and it is the duty of Muslims to prevent and condemn such acts. Hence, it is vital to effectively enforce the existing laws to minimize instances of blasphemy and to ensure that no one dares to use derogatory language against the esteemed personality of Prophet Muhammad (peace be upon him). The subsequent article provides a comprehensive overview of these issues.